Adaptive fractional-order terminal sliding mode control of rubber-tired gantry cranes with uncertainties and unknown disturbances - Cuong, Hoang Manh; Dong, Hoang Quoc; Trieu, Pham Van; Tuan, Le Anh (Mechanical systems and signal processing, 2021)
•A fractional–order control system is developed for rubber-tired gantry cranes.•The core of sliding mode control is enhanced by combining with fractional calculus and adaptive control.•The controller works well, holds robustness and adaptation when the crane faces uncertainties and unknown wind.•Simulation, experiment, and comparison to other SMC-based methods show the superiority of proposed control approach. Using three actuators for tracking five outputs, rubber-tired gantry (RTG) crane is found to be a highly under-actuated system subject to random wind due to working outdoors. Applying fractional calculus to sliding mode control (SMC), we construct an adaptive robust control system for RTG cranes under parametric variations and unknown wind. The adaptive feature is achieved by using an estimation mechanism for approximating five crane parameters and wind disturbances. The core of the sliding mode displays robust behavior against uncertainties. For comparison, another robust controller is proposed based on finite-time sliding mode. Simulation and experiment results show the superiority of adaptive fractional-order sliding mode control, in which the controller well tracks actuated states and stabilizes unactuated states despite parametric uncertainties and unknown disturbances.